Strong optical response and light emission from a monolayer molecular crystal - Huijuan Zhao (Nature Portfolio, 2019)
The optical response of inorganic two-dimensional semiconductors is dominated by Wannier-Mott excitons, but molecular systems can host localised Frenkel excitons. Here, the authors report strong optical response in a class of monolayer molecular J-aggregates due to the coherent Coulomb interaction between localised Frenkel excitons.